Willingness to pay for biodiversity conservation and climate protection: A comparative empirical analysis for Germany - Sophia Möller; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2025)
While climate change is widely considered as a major challenge for societies, another pressing global environmental problem, i.e. the loss of biodiversity, is often given less attention despite its strong negative consequences for ecosystems and thus for human life. In light of the strong interconnections between biodiversity loss and climate change, this paper compares the preferences and stated willingness to pay (WTP) for biodiversity conservation and climate protection. The empirical analysis is based on data from a broadly representative large-scale computer-assisted online survey of more than 9,000 citizens in Germany in 2021. Our data reveal a strong correlation between the perceived importance of the problems of biodiversity loss and climate change as well as between the WTP for biodiversity conservation and climate protection. However, the average WTP for climate protection is slightly higher than for biodiversity conservation according to our data. Our econometric analysis with bivariate linear and loglinear regression models as well as Tobit and binary probit models suggests that the main explanatory factors, namely environmental attitudes (i.e. environmental awareness and ecological policy identification) as well as economic preferences (i.e. altruism, trust, and patience) in addition to some socio-economic variables (e.g. equivalized income), are very similar for the WTP for biodiversity conservation and climate protection. However, for many individual characteristics (e.g., ecological policy identification, altruism, trust, patience) that are (statistically) significantly correlated with the WTP for both climate protection and biodiversity conservation, the correlations are significantly stronger for the WTP for climate protection. These estimation results, in combination with a higher average perception in our sample that climate change is an important global environmental problem, could be due to the stronger recognition of climate change and protection in the public debate (e.g., in media coverage) compared to biodiversity loss and conservation.
Keywords: Q57; Q54; 330; Biodiversity conservation; climate protection; willingness to pay; bivariate econometric models